Frequency of Anxiety after Stroke: A Systematic Review and Meta-Analysis of Observational Studies. Issue 7 (October 2013) - Burton, C. Alexia Campbell; Murray, Jenni; Holmes, John; Astin, Felicity; Greenwood, Darren; Knapp, Peter
Background and purpose: Negative psychological outcomes occur frequently after stroke; however, there is uncertainty regarding the occurrence of anxiety disorders and anxiety symptoms after stroke. A systematic review of observational studies was conducted that assessed the frequency of anxiety in stroke patients using a diagnostic or screening tool. Summary of review: Databases were searched up to March 2011. A random effects model was used to summarize the pooled estimate. Statistical heterogeneity was assessed using the I 2 statistic. Forty-four published studies comprising 5760 stroke patients were included. The overall pooled estimate of anxiety disorders assessed by clinical interview was 18% (95%confidence interval 8–29%, I 2 = 97%) and was 25% (95% confidence interval 21–28%, I 2 = 90%) for anxiety assessed by rating scale. The Hospital Anxiety and Depression Scale-Anxiety subscale 'probable' and 'possible' cutoff scores were the most widely used assessment criteria. The combined rate of anxiety by time after stroke was: 20% (95% confidence interval 13–27%, I 2 = 96%) within one-month of stroke; 23% (95% confidence interval 19–27%, I 2 = 84%) one to five-months after stroke; and 24% (95% confidence interval 19–29%, I 2 = 89%) six-months or more after stroke. Conclusion: Anxiety after stroke occurs frequently although methodological limitations in the primary studies may limit generalizability. Given the association between prevalence rates and the Hospital Anxiety and Depression Scale-Anxiety cutoff used in studies, reported rates could in fact underrepresent the extent of the problem. Additionally, risk factors for anxiety, its impact on patient outcomes, and effects in tangent with depression remain unclear.